2021
DOI: 10.1097/upj.0000000000000207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enhanced Recovery after Surgery Protocols on Opioid Prescriptions at Discharge after Major Urological Cancer Surgery

Abstract: IntroductionEarly recovery after surgery (ERAS) protocols are designed limit the use of opioids during in-patient stay to facilitate recovery and early discharge. However, there are conflicting reports of opioids prescribed at discharge to these patients. We wished to evaluate the effect of early recovery efforts on the opioid prescriptions given at discharge after major urologic cancer surgery. MethodsWe reviewed opioid prescription data from patients discharged from our facility after major urologic cancer s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Nineteen studies (8,407 patients; 4,443 in the pre- and 4,031 in the post-intervention cohort) reported sufficient data on prescribed opioids in both cohorts to allow for pooled analysis. 10–25,28,30–32 A significant reduction in prescribed opioids at discharge was noted in all except 1 study following the implementation of various interventions. The mean overall reduction in the post-intervention cohort was −67.59 MME (95% CI 54.23–80.94, p <0.001, I 2 =95%; fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Nineteen studies (8,407 patients; 4,443 in the pre- and 4,031 in the post-intervention cohort) reported sufficient data on prescribed opioids in both cohorts to allow for pooled analysis. 10–25,28,30–32 A significant reduction in prescribed opioids at discharge was noted in all except 1 study following the implementation of various interventions. The mean overall reduction in the post-intervention cohort was −67.59 MME (95% CI 54.23–80.94, p <0.001, I 2 =95%; fig.…”
Section: Resultsmentioning
confidence: 91%
“…10–32 Direct interventions to reduce opioid prescriptions were evaluated in 16 studies 11,12,14,15,18–21,25–29,31 (7,086 patients), while 6 studies 10,13,16,24,30,32 (1,818 patients) evaluated the effects of various indirect interventions. In 12 studies, 10,11,14,16,19,21,24–26,29,30,32 the procedures were categorized as major surgery, while 7 studies 12,13,18,20,22,23,27 included minor procedure and 3 studies 16,28,31 included both. All studies were either case-control or cohort studies, and there were no reports from randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 However, the association of ERAS implementation with discharge opioid prescribing is understudied, and select studies in single specialty cohorts show mixed results. 27,28…”
mentioning
confidence: 99%